Stability of High Band Gap P3HT : PCBM Organic Solar Cells Using TiOx Interfacial Layer - Kurniawan Foe; Gon Namkoong; Matthew Samson; Enas M. Younes; Ilho Nam; Tarek M. Abdel-Fattah (International Journal of Photoenergy)
We fabricated a poly[3-hexylthiophene] (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM) organic photovoltaic cells (OPCs) using TiOx interfacial layer. We performed optimization processes for P3HT : PC61BM with the TiOx layer. We found that a solution based TiOx layer coated at a spin speed of 3000 rpm improved the photon absorption of the active layer. An optimized TiOx layer was also used as the interfacial layer to investigate the stability of P3HT : PC61BM OPC. After 70 days of storage, we observed that the short-circuit current density (JSC) dropped by 16.2%, fill factor (FF) dropped by 10.6%, and power conversion efficiency (PCE) dropped approximately by 25%, while the open-circuit voltage (VOC) remained relatively stable. We found that a solution based TiOx layer synthesized using a sol-gel chemistry method was very effective in protecting the active layer from degradation.